Results of an estimation of the generalized gender differences of results of performance of the strongest swimmers at prestigious competitions. - Ganchar A.I. (Pedagogìka, Psihologìâ ta Mediko-bìologìčnì Problemi Fìzičnogo Vihovannâ ì Sportu, 2010)
The information on participation of the strongest swimmers in republican and international competitions is submitted. The level and a degree of forming of skills of navigation at sportsmen of a different floor, age and qualification is determined. Dominating differences and similarities in dynamics of parameters of swimming readiness of sportsmen are revealed. Directions of vocational training of students, perfection of special knowledge, applied skills and skills are shown. Stimulating factors of training and perfection of special knowledge of students are recommended.